Dr Karl Koenig: a brief survey of his extraordinary early years. Issue 2 (May 2014) - Jackson, Robin
Over 70 years ago, an Austrian émigré doctor – Karl Koenig – came to Scotland where he established the Camphill Movement. Today that Movement embraces over 100 communities for children and adults with developmental disabilities in at least 24 countries. One aspect of Koenig's biography that has not been explored concerns his childhood: an extraordinary omission given its inspirational character. Without an appreciation of this critical period in his life, any understanding of his very considerable achievements not least his pioneering success in establishing the Camphill Movement must be incomplete.